Genetic Variations of Fourth Exon Region of Prolactin Gene and Its Associations with Growth Traits in European Sea Bass Dicentrarchus labrax (Moronidae) - Özcan-Gökçek, E.; Işık, R. [UNESP] (Pleiades Publishing, 2023)
Abstract: European sea bass Dicentrarchus labrax (Moronidae), which has a high commercial value, is mainly produced in the Mediterranean region. Prolactin (PRL) is a member of the helix bundle protein family that is secreted in the anterior pituitary gland and has a significant role in osmoregulation and growth in teleost fish. In this study, we investigated the genetic variation of the partial sequence of 3rd, 4th introns, and 4th exon regions of the PRL gene in Dicentrarchus labrax and its association with growth traits that were reared in cage conditions. Two SNPs (g.484 A > C, g.529 T > C) and one 15 bp indel (insertion/deletion) have been found in the 3rd intron region of the PRL gene of Dicentrarchus labrax. A significant association has been identified between the total body weight and the genotypes for PRL g.529 T > C locus (р < 0.05). The heterozygote genotype of the PRL g.529 T > C locus has a significantly higher total body weight than the other genotypes in the population (p < 0.05). Association analysis indicated that this SNP in the PRL gene is correlated with growth traits and could be used for genomic selection programs in Dicentrarchus labrax breeding.
Keywords: European sea bass; growth; prolactin; SNP